Does light alcohol consumption during pregnancy improve offspring's cognitive development? - Liang, Wenbin; Chikritzhs, Tanya (Elsevier, 2012)
We posit that: (i) light alcohol consumption during pregnancy does not improve the cognitive development of human offspring and (ii) observational study outcomes indicating apparent protective effects arise from residual confounding due to socioeconomic status. Our hypotheses counter emerging hypotheses apparent in the epidemiological literature that light alcohol consumption during pregnancy improves offspring’s cognitive development. Determining the plausibility of this proposition is important given its potential to influence women’s alcohol consumption behavior during pregnancy. However, given ethical concerns, it is unlikely that a randomized control trial will be conducted to test this hypothesis. The veracity of alcohol’s purported positive effect on cognitive development is therefore explored here by comparing research evidence on light alcohol consumption to the evidence for folate and DHA supplementation intake during pregnancy. An alternative approach for further testing this hypothesis in observational studies is also suggested.